Ferritin Levels in Colombian Children: Findings from the 2010 National Nutrition Survey (ENSIN) (2016)
Low ferritin is associated with many adverse health outcomes and is highly prevalent worldwide. The aim of this study was to describe the key findings related to plasma ferritin levels to identify the prevalence and associated sociodemographic factors in a representative sample of children in Colombia, based on the 2010 National Nutrition Survey. We analyzed cross-sectional data from 6650 Colombian children between the ages of 5 and 12. Plasma ferritin levels were determined by chemiluminescence. Sociodemographic data was assessed by computer-assisted personal interview technology. All analyses were conducted considering the complex nature of the sample. Of the children assessed, 3.5% had low ferritin, defined as levels